Estrategia metodológica para mejorar la expresión oral en el idioma inglés en los estudiantes del segundo año de bachillerato en comercialización e información turística en la unidad educativa “Santa Rosa” en Santa Rosa, provincia de El Oro, año 2013. - Izquierdo Espinoza, Senovia Rocío (2013)
This research is based on a review of learning theories, reflection of pedagogical practice in the classroom and comparison of theory with everyday teaching experience. Professionals, investors, innovators, future know that English is the key that opens many doors. In Ecuador students take English classes in an average of 800 hours throughout high school and upon graduation few students who learned to just say hello, and introduce themselves.